The Factors Affecting Customer Loyalty in The Dive Tourism Industry in Indonesia: - - Ganyang, Machmed Tun (Archives of Business Research, 2022)
Abstract Diving Industry in Indonesia has huge potential needs to be managed properly in order to carrying out the concept of green tourism, but it has not been supported by the optimal performance of dive centers. That is marked by the low level of loyalty of diving tourism consumers. The purpose of this research is to analyze the effect of Green Marketing and Service Quality to Customer Satisfaction and Customer Loyalty of Diving Tourism Customer. Research Method used in this research is descriptive analysis with research design used is explanatory design. The research object is 12 (twelve) dive centers is spread on Three provinces in Indonesia. Analysis unit are experience and certified divers with total 200 respondents. Each sample from dive center is chosen proportionally. Technic Sampling is judgment sampling. The tool analysis used is statistic descriptive supported by SPSS software and statistic inferential supported by software of Lisrel Version 8,80. The research result described that practiced of green marketing, service quality have positif impact on Customer satisfantion and Customer loyalty of divers although there are still indicators that are indicating low impact. The results of the causality study state that : a) Green marketing has no significant affect on customer loyalty, b) Green marketing has significant affect on satisfaction, c) The service quality has no significant affect on customer satisfaction,d) The quality of service has no significant affect on customer loyalty, e) The customer satisfaction has significant affect on customer loyalty. Keyword: Green Marketing, Service Quality, Satisfaction, Loyalty, Dive Tourism,Indonesia